REPRODUCTIVE CYCLE OF THE ESTUARINE BIVALVE MERETRIX MERETRIX (LINN) OF THE VELLAR ESTUARY - Jayabal, R; Kalyani, M (Indian Journal of Fisheries, 2011)
The hard clam, Meretrix mereirix '(L), in VeMar estuaiy haÂ® an extendedbreeding period from February to September and the maturation of gonads takesplace immediately after spawning. Both males, which are slightly more dominant,and females attain maturity at the same size. The spat settlement starts fromMarch onwards. Among the ecological factors, salinity is found to play an importaiitrole in the reproductive cycle.